Combustion Process and Methods of Increasing the Flammability of Wooden Structures - Nabievich, G'aniev Jahongir; Abdullaevich, Kalandarov Sardor; Davronovich, Amonov Daler; Ahmad, Rayimkulov (European Journal of Life Safety and Stability (2660-9630), 2022)
This article presents the main causes of the combustion process of wooden structures and important laws of increasing the flammability. The main goal is to state that antipyretics derived from local raw materials are an effective way to increase the fire resistance of building vain structures.